A-Z of play in early childhood - Moyles, Janet R. (Maidenhead, Berkshire, England : Open University Press, 2012)
The key themes in play are explored through an A -- Z approach covering key concepts, theories / theorists, and figures. Rather than conventional chapters, there are brief sections outlining the main areas under any particular letter of the alphabet (the length dependent on the potential content for that letter). Topics range from baby play to holistic learning to kinaesthesia and therapy. This is a fun book which would be very useful on courses attempting to introduce students to all aspects of young children's play. A further feature of the book is that some well known early years people (e.g. Profs Tricia David, Carol Aubrey, Angela Anning, Lilian Katz etc) have agreed to write a very few original thoughts identifying their own passion and interest for a particular aspect of play or a particular influence in their lives.
Includes bibliographical references and indexes.
Keywords: Early childhood education -- Handbooks, manuals, etc; Play -- Handbooks, Manuals, etc